Special subject of creation criminal community (criminal organization): issues of legislation unification of Belarus and Russia - Grishko, Alexander Y. (Journal of the Belarusian State University. Law, 2020)
This article addresses the enforcement problems of criminal responsibility of the leaders of the criminal world in the Russian Federation and the Republic of Belarus. The author draws attention to the fact that in these countries there is no legitimate legal regulation of the conceptual apparatus related to the topic of thieves in law, which significantly affects the work of law enforcement and judicial bodies in counteracting the creation of criminal communities (criminal organizations) in connection with which it is proposed, by analogy with the Law of the Republic of Georgia of 12 December 2005 No. 23-54-вc «On organized crime and racket», to develop unified standards to enhance interstate influence on the organized crime, with subsequent reciprocal implementation.
Keywords: criminal community; the fight against organized crime; the leaders of the criminal world; “thieves in law”; “thieves’ world”; the criminalization of society